Cytotoxic and Mutagenic Effects and cell Viability of Polybia sericea Social Wasp Venom (Hymenoptera: Vespidae) - Soares, Eva Ramona Pereira; de Castilho, Pamella Fukuda; de Oliveira, Kelly Mari Pires; de Castro, David Tsuyoshi Hiramatsu; dos Santos, Edson Lucas; Torres, Viviana Oliveira; de Castro, Thiago Luis Aguayo; Cardoso, Claudia Andrea Lima [UNESP]; Antonialli-Junior, William Fernando [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2024)
The venom of social wasps can be a natural promising product for the development of drugs, since in recent decades studies have investigated its antimicrobial potential, anti-inflammatory, antioxidant, anticarcinogenic, among others for its future applicability in the pharmacological industry. Although some studies have already highlighted the importance of venom for this role, few species of social wasps have had the potential of their venom investigation. In this sense, the aim of this study was to evaluate the cytotoxicity, mutagenicity and cell viability of Polybia sericea (Oliver) venom. Cytotoxicity tests using Artemia salina, cell viability test using non-tumor and tumor cell lines and Ames test that assesses genetic and cellular instability were performed. The results show that the venom presents cytotoxicity, with LD50 of 22.1 μg mL-1. Mutagenicity was not identified in the Ames test at the concentrations studied. The venom did not present cytotoxicity for MRC-5 cell line, but was cytotoxic for CHO and tumor cell line B16F10-Nex2. Therefore, these tests show that P. sericea venom may have potential for pharmacological use, although other studies of cytotoxicity and with more tumor cell lines need to be developed.
Keywords: ames test; Artemia salina; drug; insecta; mutagenicity